2000
DOI: 10.1007/s11906-996-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Observational studies of antihypertensive medication use and compliance: Is drug choice a factor in treatment adherence?

Abstract: Real-world adherence to pharmacotherapy cannot be studied in the confines of the traditional clinical trial. Thus, to better understand adherence to antihypertensive medication in actual practice, a literature search was conducted to identify observational database studies of the use of antihypertensive medication. Ten studies were identified: half studied adherence patterns after initial prescriptions to patients with a new diagnosis of hypertension, and the others evaluated antihypertensive medication use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 44 publications
(46 reference statements)
1
36
0
4
Order By: Relevance
“…[18][19][20] Monane et al, 19 in a retrospective study of 8643 hypertensives, found that good compliance was inversely correlated with the use of multiple drugs and the number of medications prescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Monane et al, 19 in a retrospective study of 8643 hypertensives, found that good compliance was inversely correlated with the use of multiple drugs and the number of medications prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Psychosocial factors related to noncompliance are well-recognized problems, and have been documented in literature with mixed results. Studies have suggested that age, 17,18 sex, 18 lower socioeconomic status, severity of disease, 17 drug choice, 7,19,20 number of medications prescribed, 18,19 drug tolerability, 7,20 regimen complexity, 18,20 co-morbid medical conditions, 17,19 family support, 21 self-efficacy, intention to comply, 22 physician-patient relationship, 23 satisfaction with health care 24 and depression 25,26 are associated with compliance. However, some of these studies are limited by specific race, 17,24 usage of nonvalidated tools, 22 and failure to exclude newly diagnosed patients and patients with co-existing medical illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A commonly encountered problem is less than optimal acceptance of therapy by patients, particularly if they are not able to detect any improvement in their quality of life, leading to lack of compliance with the prescribed regimen. [9][10][11] In fact, noncompliance with the treatment regimen, particularly in the first year of treatment, is one of the primary contributors to the large number of patients with uncontrolled hypertension, 7,11,12 and more than 50% of patients who fail to achieve the goal BP levels display suboptimal compliance rather than an inadequate regimen. 10 As noncompliance most commonly takes the form of missing at least one medication dose each week ('drug holidays'), 4,7 regimens that provide a sustained duration of effect beyond 24 h may offer advantages by protecting patients against loss of BP control when doses are inadvertently omitted.…”
Section: Introductionmentioning
confidence: 99%
“…17 The more common ways to evaluate the adherence of the patients with their medication are questionnaires about the daily administration of the drug, and pill counts, with the problem that the results can be true or false. [21][22][23][24][25][26][27] Determination of drug levels in biological fluids can be a useful tool to evaluate pharmacotherapy adherence by relating the serum or plasma levels of drugs with compliance. [1][2][3] Patient with hepatic and/or renal damage can be exclude from the study, because these conditions are related with a lower drug excretion and, therefore, with higher plasmatic concentrations.…”
Section: Introductionmentioning
confidence: 99%